Gambaran Penjualan dan Investasi Obat Generik Apotek “X” Kelurahan Karang Anyar Kota Tarakan Menggunakan Analisis ABC Tahun 2022 - Ferry Fahruddin; Benazir Evita Rukaya; Syuhada Syuhada (Politeknik Kaltara, 2024)
Pharmacies have a role in providing health services and as a business that follows the principle of profitability. If drug management is inefficient, it can result in excessive drug stocks and/or running out of stock of several types of drugs. This research aims to find out how big the percentage of drugs is in the number of sales transactions and the investment value in planning drug needs using the ABC analysis method at Pharmacy